Expression and localisation of the essential copper transporter DmATP7 in Drosophila neuronal and intestinal tissues. - Burke, R.; Commons, E.; Camakaris, J. (International Journal of Biochemistry & Cell Biology, 2008)
Copper homeostasis is achieved by a combination of regulated uptake, efflux and sequestration and is essential for animal health and viability. Transmembrane copper transport proteins of the P-type ATPase family play key roles in cellular copper efflux. Here, the transcriptional and post-translational regulation of DmATP7, the sole Drosophila melanogaster ortholog of the human MNK and WND copper transport genes, is examined. An enhancer element with sufficient regulatory information to rescue DmATP7 mutant flies to adulthood is identified. This regulatory element drives expression in all neuronal tissues examined and demonstrates copper-inducible, Mtf-1 dependent expression in the larval midgut. These results support an important functional role for copper transport in neuronal tissues and indicate that regulation of DmATP7 expression is not used to limit copper absorption in toxic copper conditions. Localisation of a functional EYFP-DmATP7 fusion protein is also examined. This fusion protein localises at or proximal to the basolateral membrane of DmATP7 expressing midgut cells supporting a role for DmATP7 in export of copper from midgut cells.